2014
DOI: 10.1371/journal.pone.0103762
|View full text |Cite
|
Sign up to set email alerts
|

St John's Wort (Hypericum perforatum L.) Photomedicine: Hypericin-Photodynamic Therapy Induces Metastatic Melanoma Cell Death

Abstract: Hypericin, an extract from St John's Wort (Hypericum perforatum L.), is a promising photosensitizer in the context of clinical photodynamic therapy due to its excellent photosensitizing properties and tumoritropic characteristics. Hypericin-PDT induced cytotoxicity elicits tumor cell death by various mechanisms including apoptosis, necrosis and autophagy-related cell death. However, limited reports on the efficacy of this photomedicine for the treatment of melanoma have been published. Melanoma is a highly agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 105 publications
2
49
1
Order By: Relevance
“…Previously, we have shown that 3 lM activated HYP used during HYP-PDT induces cytotoxic effects in human melanoma cancer cells [17,18]. Therefore, a 4 h incubation time for HYP implemented in this study, was adjusted to correlate with optimal accumulation times of HYP in melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we have shown that 3 lM activated HYP used during HYP-PDT induces cytotoxic effects in human melanoma cancer cells [17,18]. Therefore, a 4 h incubation time for HYP implemented in this study, was adjusted to correlate with optimal accumulation times of HYP in melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the case of Mc, we postulate that both functions may be at play. Initially the melanin could function as an antioxidant and reduce the ROS by directing/sinking the HYP in melanosomes, as we have previously shown that HYP localizes to melanosomal membranes [17]. However, with increased oxidative stress an overwhelming oxidative burden may affect the integrity of the melanosomes and hence causes leakage of the toxic melanin intermediates, thereby leading to cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypericin, a constituent from Hypericum perforatum L., is a potent photosensitizer for clinical PDT due to its excellent photosensitizing properties, high‐quantum yield of fluorescence and singlet oxygen generation upon photoexcitation, good photostability and a relatively low dark toxicity . Cytotoxicity induced by photoexcited hypericin elicits tumour cell death by various mechanisms including apoptosis, necrosis and autophagy‐related cell death . Hypericin‐based PDT destroys the cancer cells with significantly less side‐effects compared to the current treatments like radiation and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Cytotoxicity induced by photoexcited hypericin elicits tumour cell death by various mechanisms including apoptosis, necrosis and autophagy-related cell death. [2,5] Hypericin-based PDT destroys the cancer cells with significantly less side-effects compared to the current treatments like radiation and chemotherapy. However, systemic administration and bioavailability of this photosensitizer are limited by its hydrophobic nature.…”
Section: Introductionmentioning
confidence: 99%